EMPOWERING LOCAL PRODUCT THROUGH CULTURAL GLOBALIZATION - Bastian, Tiara Putih (Journal of Social Political Sciences, 2020)
The rapid expansion of western products through cultural globalization entering Indonesia cannot be denied, this has both positive and negative sides. This paper analyzes the positive side of cultural globalization through cultural homogenization. By utilizing the homogeneity pattern of western products, Indonesian local products, especially from SMEs, has the opportunity to expand. This in turn has a positive impact on the development of Indonesia's economy so that it moves out of poverty to a middle or semi-pheri position, based on Wallarstein's World Economy theory.